Efektifitas Terapi Murottal Surat Yasin Terhadap Penurunan Tekanan Darah Pada Lansia Dengan Hipertensi (Experimental Study) - Dini Sukmalara; Qurrota A'yun; Siti Rapingah; Zuhriya Meilita; Seniawati Seniawati (LPPM STIKes BHAKTI HUSADA CIKARANG, 2026)
Introduction Hypertension is the most common disease among the elderly, resulting from degenerative changes that occur with increasing age. The most prevalent disease in older adults is hypertension, with a prevalence of 45.3% (ages 44–54 years), 55.2% (ages 56–74 years), and 69.5% (ages ?75 years). Hypertension is a major risk factor for stroke, myocardial infarction, and chronic kidney disease. One of the non-pharmacological therapies for hypertension is Qur'an Murottal Therapy, which is effective in reducing blood pressure and is free from the chemical side effects of medications. The purpose of this study was to analyze the effect of Qur'an Murottal Therapy using Surah Yasin on reducing blood pressure in elderly patients with hypertension. Methods This study used an Experimental Study with a True Experimental Design, employing a Pretest-Posttest Control Group Design consisting of an experimental group and a control group. The sampling technique used was simple random sampling, involving 30 respondents (15 in the experimental group and 15 in the control group). The results of the univariate analysis in the experimental group showed a decrease in blood pressure values of 87% after the Surah Yasin Murottal therapy intervention, whereas the control group showed no decrease (97%). The bivariate analysis using the Paired Sample T-Test showed a Sig. (2-tailed) value of 0.000 < 0.05 for both systolic and diastolic blood pressure in the experimental group. Meanwhile, in the control group, the systolic Sig. (2-tailed) value was 0.061 > 0.05 and the diastolic Sig. (2-tailed) value was 0.872 > 0.05. Conclusion There was a significant effect before and after the administration of Surah Yasin Murottal Therapy on reducing blood pressure among the elderly in the experimental group, whereas the control group showed the opposite result. Recommendation Elderly individuals with hypertension are encouraged to make Surah Yasin Murottal Therapy a regular daily activity, as it is an effective non-pharmacological therapy for controlling and reducing blood pressure. Keywords: Effectiveness, Hypertension, Murottal, Therapy, Yasin